Comparison of oxygen saturation between Term and Preterm Newborns delivered by normal versus cesarean route (Bangladesh Journal of Medical Science, 2023)
Introduction: Neonates undergo major physiologic changes during transition from intrauterine to extra-uterine period. Although, this transition is smooth mostly, 5-10% needs some assistance in breathing. The indications and timing of supplemental oxygen therapy to assist the newborn in this transition has been a matter of debate.Objective: To observe the range of oxygen saturation among healthy newborns in the first 10 minutes of life and to compare those with different gestation and mode of delivery.Materials and Methods: This cross-sectional study was conducted in the Department of Obs & Gynae, BSMMU for 9 months. All healthy neonates born by normal vaginal or cesarean delivery were included. For each newborn, oxygen saturation was recorded at 1, 5, and 10 minutes after birth and every 5 minutes thereafter till readings from both these sites crossed 90% and equalized. Parents were interviewed with a specific pre-designed and pre-tested questionnaire. Collected data were analyzed by using SPSS v20.Results: A total of 300 newborn data were analyzed. Newborns who were born by cesarean delivery had lower SpO2 than infants born vaginally (p 85%. The median SpO2 did not reach 90% until 5 minutes of life in either group. Significant difference in oxygen saturation was also found at 1, 5 & 10 minutes of life between pre-term & and term newborns (P value